2022
DOI: 10.3390/educsci12100663
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Industry 4.0 in Higher Education Using Challenge-Based Learning: An Intervention in Operations Management

Abstract: Industry 4.0 is predicted to significantly transform the jobs and skill profiles of workers. Implications for higher education may involve dramatic changes in the demand for knowledge and skills. In response to this, a Challenge-Based Learning (CBL) intervention was designed with the aim of developing working skills for the future of work on undergraduate students by embedding the Industry 4.0 theme in the Operations Management curricula. The CBL intervention was implemented in two different academic terms at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…The 3D hands on approach of LSP also showed (through students' responses in Figure 7 regarding ideation and design phase feedback) that it can address the challenge of SC 4.0 complexity. Various research indicated that the complexity of both Industry 4.0 and SC 4.0 requires higher education to adopt a learn by doing approach (Hariharasudan and Kot, 2018), through a challenge-based problem (Vilalta-Perdomo et al ., 2022) in a didactic environment (González and Calderón, 2018) to be able to teach them to students. LSP as a platform fulfills these requirements and the results presented support such a claim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D hands on approach of LSP also showed (through students' responses in Figure 7 regarding ideation and design phase feedback) that it can address the challenge of SC 4.0 complexity. Various research indicated that the complexity of both Industry 4.0 and SC 4.0 requires higher education to adopt a learn by doing approach (Hariharasudan and Kot, 2018), through a challenge-based problem (Vilalta-Perdomo et al ., 2022) in a didactic environment (González and Calderón, 2018) to be able to teach them to students. LSP as a platform fulfills these requirements and the results presented support such a claim.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in preparing students to be the future SC 4.0 mangers there is a clear need to ensure that the pedagogy and curriculum they go through will be able to take them beyond current linear and deterministic thinking, capture the evolving nature of SC as well as explain the distributive and integrated nature of these systems. Many of the current SC management instructional resources lack the capability to engage with these challenges due to their reliance on mainly passing on a body of knowledge to the students in a classical static manner (Tortorellaa et al ., 2022; Vilalta-Perdomo et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite growth in the use of Industry 5.0 technologies that support the entire teaching and learning process [38], most educational institutions still focus on ensuring students develop familiarity with the tools used within simulated work scenarios [84] rather than incorporate authentic, real-world problems that involve multiple stakeholders, including patients, clinicians, industry partners, etc. Additionally, the barriers to, and enablers of, the successful adoption and implementation of Industry 5.0 technologies to support learning and teaching activities have so far been ignored or not well documented.…”
Section: Infrastructure Resources and Technologiesmentioning
confidence: 99%
“…As a result, there will be increased demand for knowledge-based (cognitive) occupations, driven by a continuing shift from routine manual skills to non-routine, metacognition-based skills, such as problem-solving, collaboration, and leadership. However, education researchers have noted that the current research on preparing students for the future of work is still in its infancy [84,91,92]. Despite many of the digital technologies already existing in the higher education system [84,91,92], these are becoming less relevant in addressing the complex future labour market in the context of Industry 5.0.…”
Section: Strategies To Reinvent Education Pedagogymentioning
confidence: 99%
See 1 more Smart Citation